THE IMPACT OF ENVIRONMENTALLY SUSTAINABLE PRACTICES IN THE BEAUTY INDUSTRY INFLUENCES INDONESIAN GENERATION Z PURCHASING INTENTION - Jasmine Aulia, Alifa
The beauty industry in Indonesia is growing rapidly with a projected annual growth rate of 9% by 2026, driven largely by the increasing demand for beauty products. This spending shift happened especially because of the rise of Generation Z as a significant consumer group where it is changing positively towards environmentally sustainable movement. From this knowledge, it raises questions; How does refillable packaging in beauty products positively affect the purchasing intention of Indonesian Generation Z consumers in the beauty industry?, How does beauty product packaging made from eco-friendly materials (biodegradable, recycled plastics, paper) positively affect the purchasing intention of Indonesian Generation Z consumers in the beauty industry?, How do companies implementing product ingredient transparency positively affect the purchasing intention of Indonesian Generation Z consumers in the beauty industry?, How does environmentally sustainable practices in beauty companies positively affect the purchasing intention of Indonesian Generation Z consumers in the beauty industry?. This research aims to act as a guide to help leverage beauty companies among Indonesian Generation Z consumers. This research will help answer the following through quantitative data research based on a primary and secondary data collection. The findings obtained from this study, shows that Indonesian Generation Z values sustainability as their purchasing intentions are significantly affected by companies eco-friendly practices. This study highlights four main examples of ESPs such as eco-friendly packaging, refillable packaging, product ingredient transparency, and overall sustainable business practices, which affect the purchasing intention of Indonesian Gen Z, except for refillable packaging. Environmental factors related to the purchasing intention are crucial in the companies future organization plan and business objectives in determining which practical solutions to pursue. Diversity of demographic as in the geographical location, specific age group of only Generation Z, industry investigated are the limitations of this research, followed by the only utilization of quantitative methods. In some ways these limitations could restrict the collection of consumers' perspective.